2017 consensus of the Asia Pacific Heart Rhythm Society on stroke prevention in atrial fibrillation. Issue 4 (27th June 2017) - Chiang, Chern‐En; Okumura, Ken; Zhang, Shu; Chao, Tze‐Fan; Siu, Chung‐Wah; Wei Lim, Toon; Saxena, Anil; Takahashi, Yoshihide; Siong Teo, Wee
Abstract: Atrial fibrillation (AF) is the most common sustained arrhythmia, causing a 2‐fold increase in mortality and a 5‐fold increase in stroke. The Asian population is rapidly aging, and in 2050, the estimated population with AF will reach 72 million, of whom 2.9 million may suffer from AF‐associated stroke. Therefore, stroke prevention in AF is an urgent issue in Asia. Many innovative advances in the management of AF‐associated stroke have emerged recently, including new scoring systems for predicting stroke and bleeding risks, the development of non‐vitamin K antagonist oral anticoagulants (NOACs), knowledge of their special benefits in Asians, and new techniques. The Asia Pacific Heart Rhythm Society (APHRS) aimed to update the available information, and appointed the Practice Guideline sub‐committee to write a consensus statement regarding stroke prevention in AF. The Practice Guidelines sub‐committee members comprehensively reviewed updated information on stroke prevention in AF, emphasizing data on NOACs from the Asia Pacific region, and summarized them in this 2017 Consensus of the Asia Pacific Heart Rhythm Society on Stroke Prevention in AF. This consensus includes details of the updated recommendations, along with their background and rationale, focusing on data from the Asia Pacific region. We hope this consensus can be a practical tool for cardiologists, neurologists, geriatricians, and general practitioners in this region. We fully realize that there are gaps, unaddressed questions, and many areas of uncertainty and debate in the current knowledge of AF, and the physician׳s decision remains the most important factor in the management of AF.